Foreign Aid and Self-Reliance in Post- Socialist Tanzania (The Case of the Distribution of Mosquito Bed Nets) - Dmitri Bondarenko; Jason Nkybonaki; Beatrice Mosha Mkunde (Modern Africa, 2013)
Self-reliance was a cornerstone of Ujamaa socialism – the ideology of Tanzania from 1967 till the mid-1980s. In the post-Cold-War period socialist ideology was actually abandoned, together with the really valuable concept of self-reliance. As most African countries, Tanzania is crucially dependent on foreign aid. We argue that aid can play a positive part for Tanzania and countries like it, but only if it promotes their self-development which, in its turn, is possible only if a nation is or strives to become self-reliant. However, in contemporary Tanzania the culture of self-reliance has almost disappeared since national ideology has changed, and many people rely on foreign aid and national government, not on their own hard work. At the same time, the union of foreign donors and corrupt national bureaucracy results in Tanzania in aid without development that, as in the case of aid for mosquito bed nets, cannot promote self-reliance and, hence, socio-economic progress.